Immunological Characteristics between αβ TDC and γδ TDC Cells in the Spleen of Breast Cancer-Induced Mice - Silva, Polyana Barbosa; Michelin, Márcia Antoniazi; Jammal, Millena Prata; Murta, Eddie Fernando Cândido (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To evaluate the antitumoral role of γδ TDC cells and αβ TDC cells in an experimental model of breast cancer.Methods Thirty female Balb/c mice were divided into 2 groups: control group (n = 15) and induced-4T1 group (n = 15), in which the mice received 2 × 105 4T1 mammary tumor cell line. Following the 28-day experimental period, immune cells were collected from the spleen and analyzed by flow cytometry for comparison of αβ TDC (TCRαβ+ CD11c+MHCII+) and γδ TDC (TCRγδ+CD11c+MHCII+) cells regarding surface markers (CD4+ and C8+) and cytokines (IFN-γ, TNF-α, IL-12 and IL-17).Results A total of 26.53% of γδ TDC - control group (p < 0.0001) - the proportion of αβ TDC was lower in splenic cells than γδ TDC; however, these 2 cell types were reduced in tumor conditions (p < 0.0001), and the proportion of IFN-γ, TNF-α, IL-12 and IL-17 cytokines produced by γδ TDC was higher than those produced by αβ TDC, but it decreased under conditions of tumor-related immune system response (p < 0.0001).Conclusion Healthy mice engrafted with malignant cells 4T1 breast tumor presented TDC with γδ TCR repertoire. These cells express cytotoxic molecules of lymphocytes T, producing anti-tumor proinflammatory cytokines.
Keywords: immunology; breast neoplasms; immunotherapy; T-lymphocytes; receptors